2015
DOI: 10.1007/s00253-015-7001-7
|View full text |Cite
|
Sign up to set email alerts
|

A specific RAGE-binding peptide biopanning from phage display random peptide library that ameliorates symptoms in amyloid β peptide-mediated neuronal disorder

Abstract: Alzheimer's disease (AD) is an age-related neurodegenerative disorder in which amyloid β (Aβ) peptide accumulates in the brain. The receptor for advanced glycation end product (RAGE) is a cellular binding site for Aβ peptide and mediates amyloid β-induced perturbations in cerebral vessels, neurons, and microglia in AD. Here, we identified a specific high-affinity RAGE inhibitor (APDTKTQ named RP-1) from a phage display library. RP-1 bound to RAGE and inhibited Aβ peptide-induced cellular stress in human neurob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 40 publications
0
22
0
Order By: Relevance
“…Cancer signatures are distinct by type and from infections 32 , 33 . A tumor presumably presents more antigens, including neo-antigens, to the immune system and is often subject to immune suppression 34 37 .…”
Section: Resultsmentioning
confidence: 99%
“…Cancer signatures are distinct by type and from infections 32 , 33 . A tumor presumably presents more antigens, including neo-antigens, to the immune system and is often subject to immune suppression 34 37 .…”
Section: Resultsmentioning
confidence: 99%
“…FPS-ZM1 directly inhibited primary tumor growth; in addition, it blocked RAGE signaling in tumor-associated macrophages, inhibited tumor angiogenesis and inflammatory cell recruitment and inhibited metastasis to the lungs and liver (16). Another RAGE-binding peptide, RP-1, was demonstrated to inhibit Aβ-induced cellular stress in human neuroblastoma cells in vitro (43). Furthermore, Han et al (44) reported that 4,6-bisphenyl-2-(3-alkoxyanilino) pyrimidine inhibited the binding of Aβ to RAGE.…”
Section: Discussionmentioning
confidence: 99%
“…These cytokines are observed to increase accumulation of amyloid β-protein in AD by two mechanisms: (1) increased levels of pro-inflammatory cytokines inhibit phagocytosis of amyloid β-protein in AD brains thereby hindering the removal of plaque by resident microglia; (2) TNF has been shown to upregulate the production of amyloid β-protein via activation of the c-Jun N-terminal kinase (JNK)-dependent MAPK pathway, which promotes phosphorylation and cleavage of APP ( Liaoi et al, 2004 ; McAlpine and Tansey, 2008 ; Colombo et al, 2009 ; Montgomery et al, 2011 ; Cheng et al, 2014 ; Ahn et al, 2016 ; Decourt et al, 2017 ; Zhang et al, 2019 ). In addition, activation of the NF-κB pathway further increases BACE expression, resulting in increased production of amyloid β-protein ( Guglielmotto et al, 2012 ; Cai et al, 2016 ). High levels of amyloid β-protein cause IR downregulation via internalization, desensitization or direct substrate competition, which ultimately turn into insulin resistance ( Xie et al, 2002 ; Mullins et al, 2017 ).…”
Section: Insulin Resistance and Admentioning
confidence: 99%